The Influence of School Principals' Innovative Leadership and Teachers' Professional Competence on the Work Motivation of Public High School Teachers in Tarutung District - Gultom, Hotlinar; Pakpahan, Betty A.S.; Lubis, Bernard; Sitio, Robert J.T.; Gultom, Rogate.A.T (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The aims of this research are 1) to determine the influence of the principal's innovative leadership on the level of work motivation of State High School teachers in Tarutung District; 2) to determine the professional competence of teachers in increasing the work motivation of State High School teachers in Tarutung District; 3) to determine the influence of the principal's innovative leadership and teacher professional competence together on the work motivation of State High School teachers in Tarutung District. The method used in this research is a quantitative research method. The population is all teachers at State High Schools in Tarutung District spread across 3 schools totaling 90 teachers and this research is a population study. Data was collected using a closed questionnaire with 96 items. The results of data analysis show that: 1) the calculated F value > F table between the principal's Innovative leadership on Teacher Work Motivation is 42.371 > 3.07, thus it is known that there is an influence between the principal's Innovative leadership on the Work Motivation of Public High School Teachers in Tarutung District, namely amounting to 32.5%, 2) the calculated F value > F table between Teacher Professional Competency and Teacher Work Motivation, namely 28.336 > 3.07, thus it is known that there is an influence between Teacher Professional Competency on State High School Teacher Work Motivation in Tarutung District, which is equal to 24.4%, 3) the calculated F value > F table between the principal's Innovative leadership and Teacher Professional Competence on Teacher Work Motivation, namely 26.483 > 3.07, thus it is known that there is an influence between the principal's Innovative leadership and Teacher Professional Competence on Work Motivation State High School teachers in Tarutung District are 37.8%, thus Ha is accepted and H0 is rejected.